ANALISIS KINERJA ATRIBUT DI RUMAH MAKAN AYAM BAKAR MBOK JUM WAY HALIM KOTA BANDAR LAMPUNG - Yohana Fransiska Elizabet Hutajulu; Agus Hudoyo; Yuliana Saleh (Lampung University, 2023)
This study was conducted to identify the attributes that consumers value most at Mbok.Jum Way Halim Restaurant, Bandar Lampung City. There are various attributes that can be held in a restaurant. Each attribute that is held certainly costs money, if all the attributes are considered, then the restaurant will spend a lot of money. The restaurant must know what attributes are prioritized that are adjusted to what is considered important by consumers. Therefore, this research was done to determine what attributes buyers deem crucial and what attributes need to be preserved to enhance performance. This study employed a survey methodology and involved questionnaire interviews with 60 participants. Importance Performance Analysis (IPA) has been employed as the analytical technique. The study's findings demonstrated that, of the 20 attributes considered, 13 attributes are regarded as being crucial and 7 attributes that perform satisfactory. Attributes that must be preserved in their performance are the taste of the food, the size per serving, the friendliness and courtesy of the waiters, the accuracy of the presentation, the cleanliness of the tableware, the availability of parking space and the available alternatives for seating. The performance attributes that require improvement include price, the readiness of waiters to respond to consumers’ complaints, service speed, facility cleanliness, availability of water in the sink, and cleanliness of the toilet. Key words: Attributes, important performance analysis (IPA), performance, restaurant